ANALISIS PROFIL PELAJAR PANCASILA DIMENSI KETERAMPILAN BERNALAR KRITIS KELAS IV SD NEGERI 64/1 MUARA BULIAN - Faridatul Ulya; Maryono; Eka Sastrawati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to: (1) examine students’ critical thinking skills as part of the Pancasila Student Profile in Grade IV at SD Negeri 64/I Muara Bulian, and (2) identify the factors influencing critical thinking within the context of the Pancasila Student Profile in the same class. The research employed a qualitative approach with a case study design. Data on students’ critical thinking skills in the Pancasila Student Profile were collected from both students and teachers. Meanwhile, data on the factors influencing students’ critical thinking were obtained from teachers, students, and parents. Data collection techniques included observation, interviews, and documentation. The results of the study show that the critical thinking skills of Grade IV students at SDN 64/I Muara Bulian, as reflected in the Pancasila Student Profile, are generally good. Most students demonstrated the ability to understand, analyze, synthesize, evaluate, and draw conclusions effectively. A total of 20 students showed active and logical understanding of the material; 20 students were able to analyze by breaking down and comparing information; 17 students synthesized information from various sources into meaningful understanding; 16 students demonstrated logical evaluations; and 20 students were able to formulate relevant and in-depth conclusions.